775 lat Dominikanów w Gdańsku. (Gdańsk : [wydawca nieznany], 2002)
Jubileuszowy folder z tekstem dotyczącym historii dominikanów w Gdańsku.
Keywords: Dominikanie; 2001-; Gdańsk (woj. pomorskie); Druki ulotne